Capitalizing on Carbon - Jehangir Bhadha; Mark Clark; Michael Andreu; Yuchuan Fan; Tara Wade; Young Gu Her (EDIS)
This infographic illustrates the global carbon cycle and discusses sources, sinks, carbon markets, and carbon sequestration. Written by Jehangir Bhadha, Mark Clark, Michael Andreu, Yuchuan Fan, Tara Wade, and Young Gu Her, and published by the UF/IFAS Department of Agricultural and Biological Engineering, January 2023.